The Betawi Lexicon of Kinship and Greeting - Iskandarsyah Siregar; Samsur Rijal Yahaya (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Betawi people use the Betawi language to communicate in official and unofficial settings. Environmental factors are one of the reasons for the extinction of the Betawi language. this research helps provide an overview of the forms, meanings, and functions of greetings used by the Betawi people. It strengthens theories about the forms, meanings, and functions of greetings of kinship terms that already exist or have been made. This research classified as qualitative descriptive research which uses a phenomenological perspective and seeks to understand the meaning of events and human interactions in certain situations. The data obtained in this study are greeting and kinship lexicons in the Betawi language used by speakers in the outer Betawi, coastal Betawi, and central Betawi areas. Based on the research results described above, there are various forms, meanings and functions in the greeting lexicon and kinship lexicon in Betawi